Why do juveniles kill?: an ecological perspective on the developmental dynamics - Garbarino, James (The Routledge international handbook of juvenile homicide, 2024)
This chapter offers an ecological perspective on the developmental dynamics that lead to homicide on the part of youth. At the heart of this ecological perspective is the principle that context shapes the processes of cause and effect: Thus, if the question is “does X cause Y?”, the best scientific answer is almost always “it depends”. The chapter reviews several important aspects of context – the accumulation of risk factors, the role of social and cultural factors in giving developmental meaning to biological issues like temperament, the interactive balance between “adversity” and “developmental assets”, and the developmental impact of trauma.